Relationship between piperacillin concentrations, clinical factors and piperacillin/tazobactam-associated acute kidney injury. (22nd December 2022) - Tang Girdwood, Sonya; Hasson, Denise; Caldwell, J Timothy; Slagle, Cara; Dong, Shun; Fei, Lin; Tang, Peter; Vinks, Alexander A; Kaplan, Jennifer; Goldstein, Stuart L
Abstract: Background: Piperacillin/tazobactam, a commonly used antibiotic, is associated with acute kidney injury (AKI). The relationship between piperacillin concentrations and AKI remains unknown. Objective: Estimate piperacillin exposures in critically ill children and young adults administered piperacillin/tazobactam to identify concentrations and clinical factors associated with piperacillin-associated AKI. Patients and methods: We assessed piperacillin pharmacokinetics in 107 patients admitted to the paediatric ICU who received at least one dose of piperacillin/tazobactam. Piperacillin AUC, highest peak ( C max ) and highest trough ( C min ) in the first 24 hours of therapy were estimated. Piperacillin-associated AKI was defined as Kidney Disease: Improving Global Outcomes (KDIGO) Stage 2/3 AKI present >24 hours after initial piperacillin/tazobactam dose. Likelihood of piperacillin-associated AKI was rated using the Naranjo Adverse Drug Reaction Probability Scale. Multivariable logistic regression was performed to identify patient and clinical predictors of piperacillin-associated AKI. Results: Out of 107 patients, 16 (15%) were rated as possibly or probably having piperacillin-associated AKI. Estimated AUC and highest C min in the first 24 hours were higher in patients with piperacillin-associated AKI (2042 versus 1445 mg*h/L, P  = 0.03; 50.1 versus 10.7 mg/L, P  < 0.001). Logistic regression showed predictors of piperacillin-associated AKI included higher C min (OR: 5.4, 95% CI: 1.7–23) and age (OR: 1.13, 95% CI: 1.05–1.25). Conclusions: We show a relationship between estimated piperacillin AUC and highest C min in the first 24 hours of piperacillin/tazobactam therapy and piperacillin-associated AKI, suggesting total piperacillin exposure early in the course is associated with AKI development. These data could serve as the foundation for implementation of model-informed precision dosing to reduce AKI incidence in patients given piperacillin/tazobactam.